The Army of the Potomac : order of battle, 1861-1865, with commanders, strengths, losses and more - Collins, Darrell L. (McFarland & Company, Inc., Publishers, 2013)
"Work compiles information from the Official Records for a complete look at every battle and major campaign the Army of the Potomac participated in during the Civil War. Organized chronologically by battle, the numbers are broken down by corps, divisions, brigades and regiments, with commander's names down to the regimental level, unit strengths, casualties and losses"--